Synthesis, structure, and solution dynamics of UO22+-hydroxy ketone compounds [UO2(ma)2(H 2O)] and [UO2(dpp)(Hdpp)2(H2O)] ClO4 [ma = 3-hydroxy-2-methyl-4-pyrone, Hdpp = 3-hydroxy-1,2- dimethyl-4(1H)-pyridone] - Gramlich, Volker; Sigalas, Michael P.; Drouza, Chryssoula (My University, 2004)
Reaction of [UO2(NO3)2] with the hydroxy ketones 3-hydroxy-2-methyl-4-pyrone (Hma) and 3-hydroxy-1,2-dimethyl-4(1H)- pyridone (Hdpp)(Hdpp) in aqueous acidic solutions (pH ∼ 3) yields the compounds [UO2(ma)2(H2O)]·H2O (1·H2O) and [UO2(dpp)(Hdpp)2(H 2O)]ClO4 (2), respectively. X-ray diffraction shows that the geometry around the metal ion in both complexes is pentagonal bipyramid. Uranium ion in the crystal structure of 1 were found to be ligated with two chelate ma- groups and one unidentate H2O molecule (C coordination mode) at the equatorial plane, while in 2 with two single-bonded Hdpp there were one chelate dpp- and one H2O molecule (P coordination mode). Crystal data (Mo Kα; 293(2) K) are as follows: (1) monoclinic space group C2/c, a = 14.561(7) Å, b = 14.871(9) Å, c = 7.250(4) Å, β = 95.40(4)°, Z = 4; (2) monoclinic space group P21/c, a = 19.080(2) Å, b = 9.834(1) Å, c = 15.156(2) Å, β = 104.62(1)°, Z = 4. 1H NMR measurements indicate that complex 2 retains its structure in CD3CN solution; however, in DMSO-d6 both complexes adopt the C structure. Line-shape analysis for the 1H NMR peaks of 2 at various temperatures shows a fast intramolecular exchange process between the chelate dpp- and one of the single bonded Hdpp ligands and one slower exchange between all three ligands. The activation parameters and the decrease of the exchange rate by replacing unidentate ligand with DMSO indicate the dissociation of the unidentate ligand as the rate-determining step for the former exchange. Density functional calculations (DFT) support this mechanism and give a quantitative interpretation of the electronic structure of the two ligands and the geometries adopted by the complexes
Keywords: Dimethyl sulfoxide; Metal ions; Uranium dioxide; Water; Dissociation; Geometry